Uji Efektivitas Pemberian Air Kelapa dan Ekstrak Tomat pada Media Modifikasi terhadap Pertumbuhan Planlet Anggrek Hitam (Coelogyne pandurata) Secara In Vitro - SISMAWANTI DAYU MALINDA; HESTIN YUSWANTI; I PUTU DHARMA (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology), 2022)
The Effectiveness Test of Coconut Water and Tomato Extract on Modified Media for Growth of Black Orchid (C. Pandurata) In Vitro Plantlet growth in tissue culture is influenced by many factors, one of which is exogenous growth regulators applied to the media. The purpose of this study was to determine the effect of coconut water and tomato extract on modified media on the growth of C. pandurata plantlets. The research was carried out at the Ecophysiology Laboratory, Faculty of Agriculture, Udayana University, from January 2019 to April 2019. The study used a completely randomized design consisting of two factors, namely tomato extract and coconut water. The treatment consisted of 4 levels, 0 m/L, 100 ml/L, 150ml/L, 200ml/L, 16 treatment combinations were obtained with 3 replications. The results showed that the 100ml/l tomato extract treatment gave the highest increase in plantlet height, root length, number of roots, wet weight and dry weight. The 150ml/l tomato extract treatment gave the most increase in the number of leaves. Giving 150ml/l of coconut water gave the highest number of roots compared to other treatments. The interaction between of tomato extract and coconut water had no significant effect on all observed parameters.